CRITICAL THINKING SKILLS DALAM PEMBELAJARAN PAI UNTUK MENCEGAH RADIKALISME DAN BERITA HOAX (STUDI MULTISITUS DI SMAN 1 TRENGGALEK DAN SMAN 2 TRENGGALEK) - Atik Riyani; Saefudin Zuhri (JP : JURNAL PENDIDIKAN, 2022)
The phenomenon of cases of radicalism and the spread of hoax news that occurs in the scope of education is increasingly troubling. In fact, from kominfo data recorded in 2018, at least 10,449 pieces of radical content radical content were identified, rising to 11,800 pieces in 2019.. The potential of the radicalism movement I fixet it to continue to increase because the amount of radical content in cyberspace continues to grow every year. School as an educational institution, depending on the status, conditions, and needs of students, by taking the initiative, innovative and creative, interesting learning process, is responsible for the existence of elements in education and is responsible. This research uses a qualitative study approach using this type of local research and use a multi site design where the subjects studied have similar backgrounds and institutions. The results of the study proved that in both institutions teachers provide education based on critical thinking skills to make their students achieve and able to face every challenge of the progress of the times.